The conduciveness of the interior design of UP Engineering Library II for studying and reading as perceived by its users - Marco, Darrel Manuel O.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study focused on the users' perception of the conduciveness of the interior design of the UP Engineering Library II for reading and studying. It utilized the descriptive research design.
A total of one hundred library users were surveyed. Survey questionnaires were composed of four parts: 1.) profile of the library users; 2.) background about library usage; 3.) user's evaluation of the overall interior design of the library and; 4.) other comments and suggestions. The Philippine Association of Academic and Research Libraries (PAARL) Standard for 2000, the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) Standard 55, and principles of ergonomics served as the evaluation tools for the overall interior design of the Engineering Library II.
The data gathered from the survey questionnaires revealed that: 1.) 86 (86) of the library's clientele are Engineering students; 2.)users ranked the library's conduciveness for studying and reading as their top choice in using the library; 3.) users are satisfied with the availability of other special areas in the library such as the discussion rooms; 4.) users are satisfied with the overall interior design of the library and; 5.) users have comments regarding technical aspects of the library but no comments on the interior design of the library. Aside from the data gathered from the survey, the researcher also conducted an interview with the Head Librarian of the Engineering Library II, Ms. Sharon Ma. S. Esposo. Gleaned from the interview, the factors that Engineering Library II considered in its interior design are making the library environmentally-sound or "green library", conservation of resources and proper waste management, ergonomics principles, standards set by Philippine Association of Academic and Research Libraries (PAARL) and space allocation for the library users and staff.
The study recommended for the Engineering Library II and for other schools to start acknowledging the responsibility in providing a holistic library education and for LIS professionals to have further training, not only on the technical aspects but of the interior design of their libraries and information centers, as well. There should also be a documentation of the "I Love My Library" project, and study on the collection development of UP Engineering Library II, and a more in-depth study of ergonomics principles and how they affect library users.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Engineering Library II -- Use studies